Variability and interpretation of communication taxonomy during robot‐assisted surgery: do we all speak the same language?. (7th March 2018) - Raheem, Sana; Ahmed, Youssef E.; Hussein, Ahmed A.; Johnson, Amanda; Cavuoto, Lora; May, Paul; Cole, Adam; Wang, Derek; Ahmad, Basim; Hasasneh, Adam; Guru, Khurshid A.
Abstract : Objective: To investigate and analyse the different ways surgeons communicate with bedside assistants during robot‐assisted surgery (RAS). Methods: We retrospectively reviewed video and audio recordings of 26 RAS procedures (23 prostatectomies and three cystectomies). Three cameras and eight lapel microphones were used to record the operating theatre environment. We identified five common tasks and categorized them into 'specific', 'non‐specific' and 'unclear' categories. We also determined the frequency, time to execute the task, inconveniences and acknowledgements associated with each category. The most efficient category was the one that took the shortest duration to accomplish and was associated with the fewest inconveniences. Results: A total of 1 000 requests were made by three surgeons for six bedside assistants by three surgeons. The five identified tasks were: instrument change; clipping; suction; irrigation; and retraction. For instrument change, non‐specific requests were the most frequent compared with the other categories (77% vs 18% vs 5%; P < 0.001). For suction, specific requests were the most frequently used of the three categories (73% vs 27% vs 0%; P < 0.001) and this task was associated with the fewest inconveniences (38% vs 62%; P = 0.01). For clipping, irrigation and retraction, both specific and non‐specific requests were similar in terms of their frequency, action time and inconveniences. Comparing complete vs incomplete requests, incomplete requests had significantly shorter median action time (5 vs 8 s; P < 0.001) but did not significantly differ in terms of inconveniences and acknowledgement. Conclusion: To our knowledge, this is the first study to provide a detailed analysis of communication during RAS. It lays a foundation for standardized taxonomy to improve communication, surgical efficiency and patient safety.